The Effect of Brand Awareness And Service Quality on Repurchase Intention Through Customer Satisfaction of Mcdonald's Consumers in Semarang - Steven Adibroto Nainggolan; Bogy Febriatmoko (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The rapid growth of the fast-food restaurant industry in Indonesia demands effective strategies to maintain consumer loyalty, especially in the face of intense competition and shifting consumer preferences. This study aims to analyze the effect of Brand Awareness and Service Quality on Repurchase Intention with Customer Satisfaction as a mediating variable, focusing on McDonald's consumers in Semarang. Data were collected through a survey of 100 respondents using a purposive sampling technique. Respondents were McDonald's customers who had made at least two purchases in the last three months. Data analysis was conducted using Structural Equation Modeling (SEM) with SmartPLS. The findings show that Brand Awareness has a significant positive effect on Customer Satisfaction (β = 0.386; p = 0.000) but does not directly affect Repurchase Intention (β = 0.093; p = 0.425). Meanwhile, Service Quality significantly influences both Customer Satisfaction (β = 0.429; p = 0.000) and Repurchase Intention (β = 0.140; p = 0.017). Furthermore, Customer Satisfaction itself significantly drives Repurchase Intention (β = 0.307; p = 0.000) and acts as an effective mediator for the influence of both Brand Awareness and Service Quality on Repurchase Intention. This study highlights the key role of Customer Satisfaction as a bridge that connects consumer perceptions of brand and service with repeated purchasing decisions. The results are expected to provide practical input for McDonald's management to strengthen loyalty strategies through service quality improvements and brand reputation management